2022
DOI: 10.1111/mam.12299
|View full text |Cite
|
Sign up to set email alerts
|

Coyote diet in North America: geographic and ecological patterns during range expansion

Abstract: Coyotes Canis latrans have expanded their geographic range by 40% in the last 120 years, raising questions about their ecological impacts in the newly colonised areas. Despite a wealth of local knowledge on coyote diet in North America, we have little information about how and why diet might vary throughout the species' range. We conducted the first rangewide meta‐analysis of coyote diet by investigating how ecoregion, coyote mass, environmental conditions, presence of top predators and alternative food items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 82 publications
6
9
2
Order By: Relevance
“…* denotes significance of Fisher's exact test for which species had the greater use. their scat tended to contain a variety of food items, supporting an omnivorous diet as has been observed elsewhere throughout their range where they occur sympatrically with Bobcats (Jensen et al 2022, Thornton et al 2004).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…* denotes significance of Fisher's exact test for which species had the greater use. their scat tended to contain a variety of food items, supporting an omnivorous diet as has been observed elsewhere throughout their range where they occur sympatrically with Bobcats (Jensen et al 2022, Thornton et al 2004).…”
Section: Discussionsupporting
confidence: 68%
“…By contrast, Bobcats tended to consistently remain carnivorous throughout the year as has been observed in other ecosystems (Fedriani et al 2000, Major and Sherburne 1987). Coyotes were less frequently encountered on impoundments, but their scat tended to contain a variety of food items, supporting an omnivorous diet as has been observed elsewhere throughout their range where they occur sympatrically with Bobcats (Jensen et al 2022, Thornton et al 2004).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, the correlation between binary classifier-derived predation probabilities and observed predation preferences was substantively strong across all species, with Spearman's correlation coefficients ranging from 0.39 to 0.63. This finding underscores the potential for probabilistic models to accurately reflect predation preferences, both ranging between 0 and a maximum value, even with relatively small datasets and broad-scale predictions (even if that we know that trophic relationships are not stable across space and time, see for example Castañeda et al (2022) for foxes and Jensen et al (2022) for coyotes). Strikingly, I observed that for all predators there were numerous species with a high probability of predation but not observed initially as prey.…”
Section: Discussionmentioning
confidence: 82%
“…If a covariate occurred in multiple top models, we assessed its significance with the highest ranked model it occurred in. To evaluate support for our prediction that spatial overlap between a species and wild pigs is greater in seasons with high dietary overlap, we assigned each species to a general diet category: rabbits ( Sylvilagus floridanus and possibly S. aquaticus ) as small herbivore (Carter et al, 2023; Kissling et al, 2014), deer as large herbivore (Johnson et al, 1995; Kissling et al, 2014; McShea & Schwede, 1993), bobcat ( Lynx rufus ) as hypercarnivore (Neale & Sacks, 2001; Thornton et al, 2004), coyote as large mesocarnivore (Jensen et al, 2022), gray fox ( Urocyon cinereoargenteus ; Neale & Sacks, 2001; Wood et al, 1958) and raccoon ( Procyon lotor ; Melville et al, 2015; Rulison et al, 2012) as small mesocarnivore, and gray squirrel ( Sciurus carolinensis ; McShea & Schwede, 1993; Shealer et al, 1999; Steele et al, 1996), armadillo (Sikes et al, 1990; Whitaker et al, 2012), turkey (Dalke et al, 1942; Glover & Bailey, 1949), and wild pig (Kissling et al, 2014) as omnivore. We were unable to examine overlap between wild pigs and red fox ( Vulpes vulpes ), striped skunk ( Mephitis mephitis ), Virginia opossum ( Didelphis virginiana ), and fox squirrel ( S. niger ) due to our sample size criteria.…”
Section: Methodsmentioning
confidence: 99%